Resetting the epigenetic balance of Polycomb and COMPASS function at enhancers for cancer therapy. (June 2018) - Wang, Lu; Zhao, Zibo; Ozark, Patrick; Fantini, Damiano; Marshall, Stacy; Rendleman, Emily; Cozzolino, Kira; Louis, Nundia; He, Xingyao; Morgan, Marc; Takahashi, Yoh-hei; Collings, Clayton; et al.
Abstract The lysine methyltransferase KMT2C (also known as MLL3), a subunit of the COMPASS complex, implements monomethylation of Lys4 on histone H3 (H3K4) at gene enhancers.KMT2C (hereafter referred to asMLL3 ) frequently incurs point mutations across a range of human tumor types, but precisely how these lesions alter MLL3 function and contribute to oncogenesis is unclear. Here we report a cancer mutational hotspot inMLL3 within the region encoding its plant homeodomain (PHD) repeats and demonstrate that this domain mediates association of MLL3 with the histone H2A deubiquitinase and tumor suppressor BAP1. Cancer-associated mutations in the sequence encoding the MLL3 PHD repeats disrupt the interaction between MLL3 and BAP1 and correlate with poor patient survival. Cancer cells that had PHD-associatedMLL3 mutations or lacked BAP1 showed reduced recruitment of MLL3 and the H3K27 demethylase KDM6A (also known as UTX) to gene enhancers. As a result, inhibition of the H3K27 methyltransferase activity of the Polycomb repressive complex 2 (PRC2) in tumor cells harboringBAP1 orMLL3 mutations restored normal gene expression patterns and impaired cell proliferation in vivo. This study provides mechanistic insight into the oncogenic effects of PHD-associated mutations inMLL3 and suggests that restoration of a balanced state of Polycomb–COMPASS activity may have therapeutic efficacy in tumors that bear mutations in the genes encoding these epigenetic factors. Interactions between the MLL3 histone methyltransferase and the BAP1–UTX complex set the level of histone H3K27 methylation and suggest a new therapy for MLL3-mutant cancer.